Early-life stress differentially affects CA3 synaptic inputs converging on apical and basal dendrites of CA1 pyramidal neurons - Jappy, David; Sokolov, Rostislav; Dobryakova, Yulia; Krut’, Viktoriya; Maltseva, Ksenia; Fedulina, Anastasia; Smirnov, Ivan; Rozov, Andrei (Frontiers in Neural Circuits, 2025)
There is evidence that stress factors and negative experiences in early in life may affect brain development leading to mental disorders in adulthood. At the early stage of postnatal ontogenesis, the central nervous system has high plasticity, which decreases with maturation. Most likely, this high plasticity is necessary for establishing synaptic connections between different types of neurons, regulating the strength of individual synapses, and ultimately forming properly functioning neuronal networks. The vast majority of studies have examined the effects of early-life stress (ELS) on gene expression or behavior and memory. However, the impact of ELS on functional synaptic development and on the plastic properties of excitatory and inhibitory synapses are currently much less understood. Based on data obtained in a few studies it has been suggested that ELS reduces long-term potentiation (LTP) at Schaffer collateral to CA1 pyramidal cell synapses in adulthood. Nevertheless, different groups have reported somewhat contradictory results. In this report we show that ELS differentially affects LTP at CA3 to CA1 pyramidal cell inputs, at synapses on apical dendrites LTP is reduced, while LTP at synapses formed by CA3 pyramidal cells on basal dendrites remains unaffected.